2006
DOI: 10.1021/ma060886c
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Solvent Quality on the Self-Organization of Archetypical Hairy Rods−Branched and Linear Side Chain Polyfluorenes: Rodlike Chains versus “Beta-Sheets” in Solution

Abstract: We report on the nanoscale structure and solvent-induced phase behavior of two, nearly similar π-conjugated hairy-rod polymers, branched side chain poly[9,9-bis(2-ethylhexyl)fluorene-2,7-diyl] (PF2/6) and linear side chain poly[9,9-dioctylfluorene-2,7-diyl] (PFO or PF8), in good and bad (or poor) solventssdeuterated toluene and deuterated methylcyclohexane (MCH)sat 20°C. Small-angle neutron scattering (SANS) measurements exploiting contrast variation with side chain deuterated PFO polyfluorene have been employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
154
2
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(167 citation statements)
references
References 53 publications
10
154
2
1
Order By: Relevance
“…At room temperature, the optical characteristics matching those of the PF8 β phase are found for PF7 and PF9 in MCH both at high (∼1 vol %) [32] and low (∼0.002 vol %) [34] concentrations, while the same is seen for PF10 in thin films [35], with its thermal dependency following the lower T * mem [33]. The presence of sheetlike assemblies [26] or membranes [33] in PFs mixed with MCH (or PF N -MCH) is well established and discussed in terms of their internal structure [32] and macrophase separation [30], thermal behavior [30,32], and the existence of β phase [25,34,35]. Attention should also be placed on the density fluctuations or aggregation of the sheetlike assemblies.…”
Section: Kitts and Vanden Boutmentioning
confidence: 53%
See 3 more Smart Citations
“…At room temperature, the optical characteristics matching those of the PF8 β phase are found for PF7 and PF9 in MCH both at high (∼1 vol %) [32] and low (∼0.002 vol %) [34] concentrations, while the same is seen for PF10 in thin films [35], with its thermal dependency following the lower T * mem [33]. The presence of sheetlike assemblies [26] or membranes [33] in PFs mixed with MCH (or PF N -MCH) is well established and discussed in terms of their internal structure [32] and macrophase separation [30], thermal behavior [30,32], and the existence of β phase [25,34,35]. Attention should also be placed on the density fluctuations or aggregation of the sheetlike assemblies.…”
Section: Kitts and Vanden Boutmentioning
confidence: 53%
“…Only PF10 is soluble in MCH or MCH-d 14 at room temperature at the applied concentration. To achieve a complete solution at elevated temperatures and subsequent gelation [26,32] at low temperatures, the mixtures were prepared via a heating-cooling cycle. In a typical procedure the mixtures were first heated up to 80-85…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, on the basis of recent SANS investigations, it can be concluded that the PFO/MCH system contains sheetlike objects whose thickness is only 2-3 nm, corresponding to the thickness of 2-3 stiff polymers. 31 Such a structure, lacking any threedimensional order, cannot strictly be regarded as a true crystal but is closer to the anisotropic lamellar structures seen in certain ordered smectic phases. In recent unpublished SANS studies, the q range was extended up to 0.45 Å -1 , and no interference maximum or "Bragg peak" was observed.…”
Section: Optical Properties At Room Temperaturementioning
confidence: 89%